Occurrence, bioaccumulation and toxicological effect of drugs of abuse in aquatic ecosystem: A review - Chen, Like; Guo, Changsheng; Sun, Zhenyu; Xu, Jian (Environmental research, 2021)
Drugs of abuse are a group of emerging contaminants. As the prevalence of manufacture and consumption, there is a growing global environmental burden and ecological risk from the continuous release of these contaminants into environment. The widespread occurrence of drugs of abuse in waste wasters and surface waters is due to the incomplete removal through traditional wastewater treatment plants in different regions around the world. Although their environmental concentrations are not very high, they can potentially influence the aquatic organisms and ecosystem function. This paper reviews the occurrence of drugs of abuse and their metabolites in waste waters and surface waters, their bioaccumulation in aquatic plants, fishes and benthic organisms and even top predators, and the toxicological effects such as genotoxic effect, cytotoxic effect and even behavioral effect on aquatic organisms. In summary, drugs of abuse occur widely in aquatic environment, and may exert adverse impact on aquatic organisms at molecular, cellular or individual level, and even on aquatic ecosystem. It necessitates the monitoring and risk assessment of these compounds on diverse aquatic organisms in the further study. •Drugs of abuse are widespread in aquatic environment due to low removalefficiencies.•Drugs of abuse may cause toxic effects at molecular, cellular or individual level.•Drugs of abuse may bioaccumulate in aquatic organisms via aquatic food chain.•Research focusing on fate and combined effects of drugs of abuse is warranted